Book Review - Regional Policy: Theory and Practice - Patricio Alejandro Aroca Gonzalez (Investigaciones Regionales - Journal of Regional Research)
Ugo Fratesi's "Regional Policiy: Theory and Practice" represents a significant contribution to the field of regional decelopment studies, offering what is perhaps the first comprehensive treatment of regional policy that bridges theoretical foundations with practical implementarion. Published by Routledge, this ambitious volume addresses a notable gap in the literature bt providing a systematic examination of regional policy's conceptual underpinnings, operational mechanisms, and evaluation frameworks.